2017
DOI: 10.1080/14017431.2017.1385836
|View full text |Cite
|
Sign up to set email alerts
|

New onset postoperative atrial fibrillation and early anticoagulation after cardiac surgery

Abstract: POAF after cardiac surgery was associated with high risk of MACE. Early anticoagulation may be justified in POAF patients to secure a long-term outcome after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…16 POAF is an important clinical complication, and it is associated with and approximately 44% higher risk of mortality within 30 days, and even short episodes of POAF may be an indication of therapeutic anticoagulation. 17,18 In our review, the risk of POAF was reduced in the antioxidant treatment group (18% vs 28%), which correlates well with the findings of Shi et al, but we must acknowledge the very low quality of evidence of this outcome and lack of data to ensure reliable findings.…”
Section: Relation To Other Reviewssupporting
confidence: 85%
“…16 POAF is an important clinical complication, and it is associated with and approximately 44% higher risk of mortality within 30 days, and even short episodes of POAF may be an indication of therapeutic anticoagulation. 17,18 In our review, the risk of POAF was reduced in the antioxidant treatment group (18% vs 28%), which correlates well with the findings of Shi et al, but we must acknowledge the very low quality of evidence of this outcome and lack of data to ensure reliable findings.…”
Section: Relation To Other Reviewssupporting
confidence: 85%
“…The optimal anticoagulation duration for patients with elevated thromboembolic risk theoretically depends on the risk of recurrence. However, CS‐POAF strongly predicts late AF (adjusted odds ratios: 3.5–8.3) 12,13,17–19,22 …”
Section: Discussionmentioning
confidence: 99%
“…Each patient analyzed in the studies was found to have POAF for at least 24 hours duration. The exceptions were the Maaroos study and the Glotzer study, where patients with POAF were found to have POAF for at least 5 minutes and 6 minutes, respectively [11,12]. Most of our patients in this study included post cardiac surgery patients, either post coronary artery bypass graft or post valvular surgery [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The exceptions were the Maaroos study and the Glotzer study, where patients with POAF were found to have POAF for at least 5 minutes and 6 minutes, respectively [11,12]. Most of our patients in this study included post cardiac surgery patients, either post coronary artery bypass graft or post valvular surgery [11][12][13][14]. The exceptions were the Makhija and Butt studies, which studied patients involved in non-cardiac surgery [10,15].…”
Section: Discussionmentioning
confidence: 99%